Kesenjangan Gender : Perempuan Dalam Memperoleh Hak Politik - Gopin Pamungkas; Intan Agristin Nuraini (CV. ITTC INDONESIA, 2024)
The gender gap occurs mainly because of culture or cultures such as patriarchal culture which is dominant in the reality of society and even countries, which means that it is not easy to change the view that politics is an important public domain and can be entered by women. The literature study method used in writing this article is to collect and analyze secondary data from various literature sources. Currently, there are many regulations that regulate women's rights, but in real life, women are still often given limitations, especially in terms of obtaining or gaining access to the world of politics. Women's political rights are still very low compared to men's political rights because they are considered unable to compete in several respects.